Street cries in English and Indonesian with special reference to Makassarese - Andi Hajar (Center for Humanities and Innovation Studies, 2019)
Street vendors’ activities are interesting phenomena to be analyzed. Their cries (calls) in the streets, called street cries, existed since a long time ago. This study aims at investigating the forms and characteristics of street cries in Indonesian (Makassarese) compared to English. This study is a comparative study which uses descriptive qualitative in analyzing data. Indonesian (Makassarese) street cries were noted, recorded, and transcribed. Firstly, the result of this study shows that both Indonesian (Makassarese) and English vendors always mention the name of commodities and services they provided. Sometimes English vendors mention their prices and qualities. Secondly, the forms of Indonesian (Makassarese) street cries compared to English street cries almost the same. Some of Indonesian (Makassarese) street cries have brief (short) forms, and some of them are long, and vice versa. Thirdly, the characteristics of Indonesian (Makassarese) and English street cries mostly the same. They are using repetitive words, parallelism, degenerated (shortened) words, lengthened cries, participatory engagement, terms of address, and code-switching.